The international law of the sea - Rothwell, Donald , 1959-; Stephens, Tim (Oxford : Hart Publishing, 2010)
This book is a critical overview of the 1982 United Nations Convention on the Law of the Sea and analyses subsequent developments that supplement it
1. The history and sources of the international law of the sea -- 2. Coastal waters -- 3. Territorial sea and contiguous zone -- 4. The exclusive economic zone -- 5. The continental shelf -- 6. The deep seabed -- 7. High seas -- 8. Archipelagic states -- 9. Landlocked and geographically disadvantaged states -- 10. Navigational rights and freedoms -- 11. International straits and archipelagic navigation -- 12. Military uses of the oceans -- 13. Marine resource management -- 14. Marine scientific research -- 15. Marine environmental protection -- 16. Delimitation of maritime boundaries -- 17. Maritime regulation and enforcement -- 18. Dispute settlement in the law of the sea -- 19. Oceans governance
Includes bibliographical references and index
Keywords: Law of the sea; Maritime law